Safe in My Garden: Reduction of Mainstream Flow and Turbulence by Macroalgal Assemblages and Implications for Refugia of Calcifying Organisms From Ocean Acidification - Louise Kregting; Damon Britton; Craig N. Mundy; Catriona L. Hurd (Frontiers in Marine Science, 2021)
Macroalgae, with their various morphologies, are ubiquitous throughout the world’s oceans and provide ecosystem services to a multitude of organisms. Water motion is a fundamental physical parameter controlling the mass transfer of dissolved carbon and nutrients to and from the macroalgal surface, but measurements of flow speed and turbulence within and above macroalgal canopies are lacking. This information is becoming increasingly important as macroalgal canopies may act as refugia for calcifying organisms from ocean acidification (OA); and the extent to which they act as refugia is driven by water motion. Here we report on a field campaign to assess the flow speed and turbulence within and above natural macroalgal canopies at two depths (3 and 6 m) and two sites (Ninepin Point and Tinderbox) in Tasmania, Australia in relation to the canopy height and % cover of functional forms. Filamentous groups made up the greatest proportion (75%) at both sites and depth while foliose groups were more prevalent at 3 than at 6 m. Irrespective of background flows, depth or site, flow speeds within the canopies were <0.03 m s –1 – a ∼90% reduction in flow speeds compared to above the canopy. Turbulent kinetic energy (TKE) within the canopies was up to two orders of magnitude lower (<0.008 m 2 s –2 ) than above the canopies, with higher levels of TKE within the canopy at 3 compared to 6 m. The significant damping effect of flow and turbulence by macroalgae highlights the potential of these ecosystems to provide a refugia for vulnerable calcifying species to OA.

Seasonal and site-specific variation in the nutritional quality of temperate seaweed assemblages: implications for grazing invertebrates and the commercial exploitation of seaweeds - Damon Britton; Matthias Schmid; Andrew T. Revill; Patti Virtue; Peter D. Nichols; Catriona L. Hurd; Craig N. Mundy (Journal of Applied Phycology, 2021)